2004
DOI: 10.1111/j.1740-8261.2004.04025.x
|View full text |Cite
|
Sign up to set email alerts
|

Material in the middle ear of dogs having magnetic resonance imaging for investigation of neurologic signs

Abstract: The aim of this study was to determine the prevalence and potential significance of finding material in the middle ear of dogs having magnetic resonance (MR) imaging. Of 466 MR studies reviewed, an increased signal was identified in the tympanic bulla in 32 (7%) dogs. Cavalier King Charles spaniels, Cocker spaniels, Bulldogs, and Boxers were over-represented compared to the population of dogs having MR imaging. Five (16%) dogs had definite otitis media and one (3%) had a meningioma invading the middle ear. Of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
87
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(96 citation statements)
references
References 20 publications
7
87
1
1
Order By: Relevance
“…2,4 A previous study using MRI reported a prevalence of 7% for middle ear effusion in dogs that presented for neurologic signs. 5 In cats, a prevalence of 34% for subclinical middle ear disease has been reported. 6 A common cause of otitis media in dogs is as an extension of chronic otitis externa.…”
Section: Introductionmentioning
confidence: 99%
“…2,4 A previous study using MRI reported a prevalence of 7% for middle ear effusion in dogs that presented for neurologic signs. 5 In cats, a prevalence of 34% for subclinical middle ear disease has been reported. 6 A common cause of otitis media in dogs is as an extension of chronic otitis externa.…”
Section: Introductionmentioning
confidence: 99%
“…2 Radiography, computed tomography (CT), and magnetic resonance imaging (MRI) represent valuable instruments to diagnose common middle ear diseases such as otitis media, (inflammatory) polyps, cholesteatomas, and neoplasms. [3][4][5][6] Diagnostic imaging findings commonly associated with middle ear disease include changes in the contour of the tympanic bulla, bone proliferation and/or osteolysis, or the presence of abnormal material in the middle ear cavity. 3,4 Occasionally, imaging findings of questionable clinical significance, formerly known as "otolithiasis," are observed on radiographs or CT scans of the tympanic cavities of dogs with variable signs of otitis media.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] Diagnostic imaging findings commonly associated with middle ear disease include changes in the contour of the tympanic bulla, bone proliferation and/or osteolysis, or the presence of abnormal material in the middle ear cavity. 3,4 Occasionally, imaging findings of questionable clinical significance, formerly known as "otolithiasis," are observed on radiographs or CT scans of the tympanic cavities of dogs with variable signs of otitis media. 7,8 "Otolithiasis" refers to the presence of rounded, smooth, sessile, hyperattenuating structures resembling mineral concretions with diameters of up to several millimeters on bulla CT scans of dogs.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas otitis media/interna is usually associated with clinical signs (Little and others 1991), in CKCS this finding is almost invariably incidental during MRI scanning for neurologic diseases (Lu and others 2003, Owen and others 2004). The condition has previously been termed ‘primary secretory otitis media’ (PSOM) and has been associated with various neurologic signs and pain (Stern-Bertholtz and others 2003).…”
mentioning
confidence: 99%